ANALISIS MICROTEACHING TAHAP PEMBUKAAN PADA MAHASISWA PGSD DALAM MATA KULIAH PSAP MATEMATIKA SD - Wiyun Philipus Tangkin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The implementation of microteaching on the PSAP (Learning Assessment Strategy Planning) Elementary School Mathematics course is aimed to teach the students pedagogical competence as prospective elementary school teachers. The study in this article is aimed to analyze the results of the microteaching implementation, especially at the opening stage, which was carried out by prospective teacher students at the Elementary School Teacher Education study program of Pelita Harapan University. It is required that the results of the study can be used as an evaluation for material, especially for lecturers to improve teaching strategies in this course. The research method used was a descriptive quantitative method with research instruments of a microteaching assessment rubric, the results of lecturer observations, and the results of students’ microteaching reflections. Quantitative data were obtained from the average value of the microteaching assessment rubric, which was then converted into a qualitative form by comparing it with the results of microteaching reflections. In the opening stage of microteaching, there are four criteria a) attracting students' attention before starting learning, b) conveying learning objectives, c) reviewing lessons, and d) motivating students. The results obtained by the researchers on microteaching of PGSD students batch 2019 were already good with the percentage for the opening stage of the criteria "attracting students' attention before starting learning 92.86% in the very good category, the criteria of “delivering learning objectives” 69.29% in enough category, the criteria for “reviewing lessons” 68.57% in enough category, and the criteria for "motivating students" 87.14% in the very good category. Based on the percentage of the four criteria at the opening stage of microteaching, it could be seen that the criteria that needed to be improved were the competency to convey learning objectives and the competency to review the lessons.